ENGLISH BLENDS FOUND DURING THE COVID-19 PANDEMIC - Giyatmi, Giyatmi; Wijayava, Ratih; Arumi, Sihindun (Universitas Samudra, 2023)
Covid-19 pandemic seems to give us blessing disguise to the size of English vocabulary, one of which is blends. This study aims at describing the types and meanings of English blends found during the Covid-19 pandemic by using blends classification from Mattiello’s theory i.e. morphotatic as well as morphological and graphic. This research belongs to a descriptive qualitative study. The research data are English blends found in 9 articles on websites. The data collection techniques used in this research are documentation and content analysis. Technic of data analysis is carried out in three stages, namely (1) data reduction which is carried out when there are same data, (2) data display which is presented in table, (3) drawing conclusions. The researchers found 49 data of English blends. Morphotactically, the researchers found 11 total blends (with 2 blends forming processes) and 38 partial blends (with 3 blends forming processes). Morphologically and graphically, the researchers found 7 overlapping blends and 42 non-overlapping blends.